Urological management of the patient with traumatic spinal cord injury - Persu, C (J Med Life, 2009)
Traumatic spinal cord injury is a very comprehensive subject, debated in many scientific papers. It interests various medical specialties, but also other sciences, like economy, psychology or social science. The patient having a motoric disability, with sphincter troubles and other associated pathologies secondary to a traumatic lesion of the spinal cord, represented a social problem from the antiquity. The first centers dedicated exclusively to these patients were established during Napoleon. Nevertheless, a systematic approach to these patients was not possible before the end of the Second World War, when scientific and economic development made possible the establishment of medical facilities specialized in the complex evaluation and treatment of patients with spinal cord injury (SCI). Between the two world wars, physicians were concentrating their efforts to keep these patients alive, considering that the main target was to treat or prevent complications which could be fatal to the patient. The first scientific papers underlining the essential place of lower urinary tract disorders in the vital prognostic of the SCI patient are dating back to this time. In modern times, the target for every patient with SCI should be social reinsertion and obtaining as much autonomy as possible. The physician needs to tune up his treatment according to this factor. The continuous evolution of medicine, alongside with technical progress and the development of modern social security have created the premises for a real quality of life of the paraplegic or even quadriplegic patient. The lower urinary tract becomes not only a key for prolonged survival, but also one of the most important elements for social reinsertion [1].